Synthesis and performance evaluation of various metal chalcogenides as active anodes for direct urea fuel cells. (October 2021) - Sayed, Enas Taha; Abdelkareem, Mohammad Ali; Bahaa, Ahmed; Eisa, Tasnim; Alawadhi, Hussain; Al-Asheh, Sameer; Chae, Kyu-Jung; Olabi, A.G.
Abstract: Metal chalcogenides have received significant attention as electro-catalysts in different applications, due to their superior electrical conductivity and good thermal and mechanical stabilities. In this work, the optimum monocrystalline Ni-P and Ni-C, C (Se, S, O) nanosheet (NS), prepared on nickel foam as standalone anodes for urea fuel cells was introduced. The activity was investigated ex-situ and in-situ the cell. The results demonstrated that the non-oxide metal forms, i.e., Ni–P, Ni–S, and Ni–Se, have superior oxidation activity than the Ni layered double hydroxide (Ni-LDH) and Ni–O. In addition, Ni–Se showed the most superior urea oxidation activity among all prepared catalysts. Although the onset potential of all the samples was around 0.35 V vs Ag/AgCl, a steady current of 195 mAcm −2 was recorded after 120 min using Ni–Se, which is two times higher than that of Ni–S, five times higher than Ni–O, and ten times higher than Ni-LDH. The superior activity of the Ni–Se was related to its unique crystalline structure and the high porous morphology. The performance of Ni–Se electrode under actual direct urea fuel cell (DUFC) operation using a nonprecious a Prussian blue cathode revealed 33 mWcm −2 power, which is, one of the highest power outputs in DUFCs equipped with Ni-based anodes at room temperature, as far as the authors know. Highlights: Optimum monocrystalline Ni-M, M (Se, S, P, O) nanosheet was prepared on Ni foam. The oxidation activity towards urea examined ex-situ and in-situ the fuel cell. Ni–Se demonstrated superior urea oxidation activity. Using Ni–Se and Prussian blue electrodes, a power output of 33 mWcm −2 is obtained.